Non-invasive Ventilation in Children With Neuromuscular Disease - Fauroux, Brigitte; Khirani, Sonia; Griffon, Lucie; Teng, Theo; Lanzeray, Agathe; Amaddeo, Alessandro (Frontiers in Pediatrics, 2020)
The respiratory muscles are rarely spared in children with neuromuscular diseases (NMD) which puts them at risk of alveolar hypoventilation. The role of noninvasive ventilation (NIV) is then to assist or “replace” the weakened respiratory muscles in order to correct alveolar hypoventilation by maintaining a sufficient tidal volume and minute ventilation. As breathing is physiologically less efficient during sleep, NIV will be initially used at night but, with the progression of respiratory muscle weakness, NIV can be extended during daytime, preferentially by means of a mouthpiece in order to allow speech and eating. Although children with NMD represent the largest group of children requiring long term NIV, there is a lack of validated criteria to start NIV. There is an agreement to start long term NIV in case of isolated nocturnal hypoventilation, before the appearance of daytime hypercapnia, and/or in case of acute respiratory failure requiring any type of ventilatory support. NIV is associated with a correction in night- and daytime gas exchange, an increase in sleep efficiency and an increase in survival. NIV and/or intermittent positive pressure breathing (IPPB) have been shown to prevent thoracic deformities and consequent thoracic and lung hypoplasia in young children with NMD. NIV should be performed with a life support ventilator appropriate for the child’s weight, with adequate alarms, and an integrated (± additional) battery. Humidification is recommended to improve respiratory comfort and prevent drying of bronchial secretions. A nasal interface (or nasal canula) is the preferred interface, a nasobuccal interface can be used with caution in case of mouth breathing. The efficacy of NIV should be assessed on the correction of alveolar ventilation. Patient ventilator synchrony and the absence of leaks can be assessed on a sleep study with NIV or on the analysis of the ventilator’s in-built software. The ventilator settings and the interface should be adapted to the child’s growth and progression of respiratory muscle weakness. NIV should be associated with an efficient clearance of bronchial secretions by a specific program on the ventilator, IPPB, or mechanical insufflation-exsufflation. Finally, these children should be managed by an expert pediatric multi-disciplinary team.